Aging With Grace for People Living With HIV: Strategies to Overcome Leaky Gut and Cytomegalovirus Coinfection. (1st February 2022) - Routy, Jean-Pierre; Royston, Léna; Isnard, Stéphane
Abstract: The intestinal epithelial layer acts as a mechanical and functional barrier between the intraluminal microbiota and the immunologically active submucosa. A progressive loss of gut barrier function (leaky gut) leads to enhanced translocation of microbial products, which in turn contributes as endotoxins to inflammaging. Th17 T cell represents the main immune sentinels in the gut epithelium, preventing aggression from commensal and pathogenic microbes. As HIV infection deeply affects gut Th17 function and increases gut permeability, microbial translocation occurs at high level in people living with HIV (PLWH) and has been associated with the development of non-AIDS comorbidities. Although the inflammatory role of endotoxins like lipopolysaccharide produced by Gram-negative bacteria is well-established, fungal products such as β-D-glucan emerge as new contributors. In addition, PLWH are more frequently infected with cytomegalovirus (CMV) than the general population. CMV infection is a well-described accelerator of immune aging, through the induction of expansion of dysfunctional CD8 T-cells as well as through enhancement of gut microbial translocation. We critically review immune mechanisms related to bacterial and fungal translocation, with a focus on the contribution of CMV coinfection in PLWH. Improving gut barrier dysfunction, microbial composition, and reducing microbial translocation constitute emerging strategies for the prevention and treatment of HIV-associated inflammation and may be relevant for age-related inflammatory conditions.